Evaluation of the mexican university student experience in innovative exhibition formats - Otero-Escobar, Alma (2025)
Currently, traditional presentation methods in higher education have limitations in motivating and actively engaging students. This situation raises the need to integrate innovative formats that promote a more dynamic learning experience. The study aimed to evaluate student satisfaction, learning, and experience when using these innovative formats instead of conventional ones. A mixed approach with a non-experimental and cross-sectional design was adopted, administering a questionnaire with Likert-scale and open-ended questions to 79 students from the University of Veracruz. The results showed that the majority perceived the formats as more motivating, interactive, and effective in improving comprehension and communication. Strong and positive correlations were identified between motivation and entertainment (r = 0.87), understanding and deepening (r = 0.86), as well as between learning facilitation and understanding (r = 0.88). Moderate correlations were also found between interaction and creativity (r = 0.79) and interaction and motivation (r = 0.72). In contrast, weak, negative correlations were found between prior experience and motivation (r = -0.02) and between experience and enjoyment (r = -0.11). Some students faced challenges related to the use of digital tools, content editing, and teamwork. It is concluded that while innovative formats promote more student-centered learning, their implementation must consider technological training and accessibility to maximize their educational impact.